Lack of Genetic Influence on the Innate Inflammatory Response to Helicobacter Infection of the Gastric Mucosa - Nedrud, John G.; Czinn, Steven J.; Ding, Hua; Zagorski, Brandon M.; Redline, Raymond W.; Twaddell, William; Blanchard, Thomas G. (Frontiers in Immunology, 2012)
Helicobacter pylori (H. pylori) is a bacterial pathogen that resides at the gastric mucosa and has a world-wide prevalence of over 50%. Infection usually lasts for the life of the host, and although all infected individuals will develop histologic gastritis only a subset will develop symptomatic gastritis, peptic ulcer disease, gastric MALT lymphoma, or gastric adenocarcinoma. The bacterial and host factors that determine clinical outcome and influence the development of widely varying diseases have not been elucidated. We compared disease in Helicobacter-infected SCID mice on different genetic backgrounds with their corresponding immunocompetent partners to determine if the genetics of the host significantly impacts the innate inflammatory outcome, independent of variations in bacterial virulence factors. BALB/c SCID and C57BL/6 SCID mice developed equivalent histologic gastritis by eight weeks of infection. Immunocompetent BALB/c mice and C57BL/6 mice developed significantly lower or higher degrees of inflammation respectively. Innate inflammation in immunodeficient mice on the C57BL/6 background remained low even in the absence of the regulatory cytokine IL-10. These results demonstrate that adaptive immunity is not required for the generation of low level inflammation in response to Helicobacter infection and that the degree of inflammation is consistent among different genetic backgrounds. Additionally, this inflammation is limited even in the absence of regulatory T cells.